19PJAK3 defines a unique molecular subtypes of East Asian non-small cell lung cancer patients. (7th November 2019) - Xu, C; Wang, W; Zhang, Q; Zhuang, W; Zhu, Y; Huang, Z; Chen, G; Fang, M; Lv, T; Song, Y
Abstract: Background: Recently, the Janus kinase 3 (JAK3) tyrosine kinase, is a well-known tumor-related gene in the JAK/STAT pathway. While the genetic variability of JAK3 mutations non-small cell lung cancer (NSCLC) patients is unclear. The aim of this study is to investigate mutations and prognosis of NSCLC harboring JAK3 mutations. Methods: A total of 938 patients with non-small-cell lung cancer were recruited between July 2012 and December 2016. The status of JAK3 mutations and other genes were detected by next generation sequencing. Results: JAK3 gene mutation rate was 1.60% (15/938) in non-small cell lung cancer, including L928del (1 patient), K964N (1 patient), L857M (1 patient), R537L (1 patient), C416F (1 patient), P479H (1 patient), T21M (1 patient), S1124L (1 patient), S340W (1 patient), S398C (1 patient), V28L (1 patient), Q1058R (1 patient), E694Rfs*10 (1 patient), S1000* (1 patient) and A853S (1 patient), and median overall survival (OS) for these patients was 15.0 months. Among them, all patients were JAK3 gene with co-occurring mutations. Briefly, patients with (n = 2) or without (n = 13) co-occurring EGFR mutations had a median OS of 14.5 months and 15.0 months respectively (P = 0.56); patients with (n = 14) or without (n = 1) co-occurring TP53 mutations had a median OS of 13.0 months and 20.0 months respectively (P = 0.52); patients with (n = 4) or without (n = 11) co-occurring KRAS mutations had a median OS of 11.0 months and 15.0 months respectively (P = 0.78); patients with (n = 3) or without (n = 12) co-occurring RBM10 mutations had a median OS of 17.0 months and 15.0 months respectively (P = 0.70). Conclusions: Mutation type of JAK3 has a potential for predicting the course of the disease and might contribute to management individualization of NSCLC patients. EGFR, TP53, KRAS and RBM10 gene accompanied may have less correlation with JAK3 mutation in NSCLC patients. Legal entity responsible for the study: Chunwei Xu. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.